The NiAl mixed oxides: The relation between basicity and SO2 removal capacity - Zhao, L.; Li, X.; Qu, Z.; Zhao, Q.; Liu, Shaomin; Hu, X. (Pergamon, 2011)
A series of NiAl mixed oxides derived from hydrotalcite-like compounds were prepared by a urea hydrolysis method, and characterized by TGA, XRD, SEM, CO2-TPD, N2 adsorption/desorption and XPS techniques. The SO2 adsorption capacity of the materials correlated closely with their basicity and active oxygen species on the surface, as estimated by a volumetric method. The NiAl mixed oxide with the optimal Ni/Al molar ratio of 3 showed the best performance of SO2 adsorption. Moreover, its adsorption equilibrium of a type I isotherm and pore opening in the quasi-micropore region significantly improve the adsorption performance for low-concentration SO2.